GAMBARAN PEMAHAMAN PASIEN PENYAKIT JANTUNG KORONER (PJK) DALAM PENGGUNAAN OBAT TROMBOLITIK DI POLI JANTUNG RSUD ARIFIN ACHMAD PROVINSI RIAU - Marwin Didik Antoro; Erwin Erwin; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Coronary heart disease is the term that reffering to heart disease caused by decrease the oxygen supply to cardiacmuscle. This research is to describe comprehension of patients with coronary heart disease in using trombholytics witchis conducted at heart poly room at RSUD Arifin Achmad Riau Province. This research aim is simple derscriptive with30 samples taken based on iclusion criteria by using purposive sampling technique. The tools in this research isquestionnaire. Analysis in this research was univariate analysis to describe distribution of frequencies characteristicrespondents and distribution of frequencies comprehension patient with coronary heart disease about drug useprocedure, side effect, monitoring of drug use, and initial action. The result of this research showed most ofrespondents are in the age range 56-65 years were 14 respondens (46,6%), most of respondents are woman 16respondents (53,7%), the most respondents have last education SMA 9 respondents (30%), most of respondents does notwork 14 respondents (46,7%). Comprehension respondents about drug use procedure majority were good 23respondents (73,7%), about side effect balance between good and not good 15 respondents (50%), aboutcomprehension monitoring of drug use majority were good 28 respondents (93,3%), and about initial action majoritywere good 27 respondents (90%).The result of this research recomended to the hospital istitution for to improveeducation programme about medicine use especially trombholytics for increase patient comprehension.Key words: Comprehension, Coronary heart disease, trombholytics